Strømme Syndrome Is a Ciliary Disorder Caused by Mutations in CENPF. Issue 4 (9th February 2016) - Filges, Isabel; Bruder, Elisabeth; Brandal, Kristin; Meier, Stephanie; Undlien, Dag Erik; Waage, Trine Rygvold; Hoesli, Irene; Schubach, Max; de Beer, Tjaart; Sheng, Ying; Hoeller, Sylvia; Schulzke, Sven; et al.
Abstract : Using whole exome sequencing we identfied compound heterozygous mutations in the centrosome gene CENPF in the siblings originally described with Strømme syndrome and two unrelated siblings with a severe phenotype overlapping that of Strømme syndrome and ciliary disorders. Strømme syndrome is an autosomal recessive disease presenting with a wide phenotypic spectrum. A key clinical sign for the recognition of CENPF‐related phenotypes may be the occurrence of intestinal atresia. ABSTRACT: Strømme syndrome was first described by Strømme et al. (1993) in siblings presenting with "apple peel" type intestinal atresia, ocular anomalies and microcephaly. The etiology remains unknown to date. We describe the long‐term clinical follow‐up data for the original pair of siblings as well as two previously unreported siblings with a severe phenotype overlapping that of the Strømme syndrome including fetal autopsy results. Using family‐based whole‐exome sequencing, we identified truncating mutations in the centrosome gene CENPF in the two nonconsanguineous Caucasian sibling pairs. Compound heterozygous inheritance was confirmed in both families. Recently, mutations in this gene were shown to cause a fetal lethal phenotype, the phenotype and functional data being compatible with a human ciliopathy [Waters et al., 2015 ]. We show for the first time that Strømme syndrome is an autosomal‐recessive disease caused by mutations in CENPF that can result in a wide phenotypic spectrum.